“Diseño de Iconografía a partir de la memoria histórica del sacha runa, personaje Autóctono de la Parroquia de Chugchilán” - Chicaiza Villegas, Alexis Darío (2023)
The purpose of this research was to design iconographies taking as a reference the historical memory of Sacha Runa, an autochthonous character from the Chugchilán parish. Through this, due to the lack of interest of the people in the festivity of the disguised, like the character, there has been a lack of information about the history, origin and components of the clothing that the Sacha Runa possesses. This led to the need to publicize the traditional identity, looking for new ways to represent the character through two-dimensional graphic solutions. Therefore, the objective that was raised in the investigation was to design iconography from the character, thus allowing to implement the iconographic compositions in various supports, whether textile or craft.